Cu2+ & Pb2+ removal by chemically modified silica gel with amidoxime / Eddy Mohd Farid Mohd Yusslee, Md. Lutfor Rahman and Sazmal Effendi Arshad - Mohd Yusslee, Eddy Mohd Farid; Rahman, Md. Lutfor; Arshad, Sazmal Effendi (Universiti Teknologi MARA, Pulau Pinang, 2015)
Chemically modified silica gel with amidoxime group was synthesized by silanization with 3-aminopropyltriethoxysilane (APTES) followed by an addition of acrylonitrile (AN) monomer to produce acrylonitrile modified silica (AN-SiO2). The product undergoes amidoximation reaction after being treated with alkaline hydroxylamine hydrochloride solution to produce amidoxime modified silica (Ami-SiO2). The final product was used as an adsorbent for copper(II) and lead(II) metal ions removal. All the structures of adsorbent and intermediate were characterized by FT-IR, SEM and elemental analysis to justify the presence of organic groups during and after modification. The optimum conditions for the removal of both metals at an initial concentration of 50 mg/L were 2 g/L of dose, pH6 and 2 hours of contact time. The removal of Cu2+ and Pb2+ by Ami-SiO2 was substantially higher compared to its unmodified form. A significant binding property of metal ions by the adsorbent at the optimum conditions was observed and the maximum adsorption capacities for Cu2+ and Pb2+ were 24.88 mg/g and 23.87 mg/g, respectively. The sorption capacities of metal ions by Ami-SiO2 were pH-dependent, and the selectivity of the adsorbent towards Cu2+ was higher compared to Pb2+. The rate of exchange was rapid, which was t1/2 < 10 min for both of Cu2+ and Pb2.